2022
DOI: 10.1145/3492856
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Conceptual Framework for Understanding the Challenges in Refugee Re-settlement

Abstract: Upon arrival to a host community, refugees and asylum seekers face immense challenges to rebuild their social capital that is critical in the process of their resettlement. Developing a holistic understanding of these challenges can provide significant opportunities to inform designers and services providers working with this demography. We adopt the lens of social capital coupled with an inquiry into the heterogeneity of refugees and asylum seekers to gain a holistic understanding of various challenges that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 90 publications
2
8
0
Order By: Relevance
“…Participants were also quick to clarify that in developing these services, it is important to recognize the diversity of refugee interpretive service needs with respect to multiple dialects, cultural norms, and regional values or shared histories that may exist within one linguistic group (e.g., within the Arab-speaking refugee population in Maryland). These points echo findings from the work of others (Almohamed et al, 2022) that emphasize the need to take into account both the diversity of refugees and the impact of their culture and religion in envisioning future solutions.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Participants were also quick to clarify that in developing these services, it is important to recognize the diversity of refugee interpretive service needs with respect to multiple dialects, cultural norms, and regional values or shared histories that may exist within one linguistic group (e.g., within the Arab-speaking refugee population in Maryland). These points echo findings from the work of others (Almohamed et al, 2022) that emphasize the need to take into account both the diversity of refugees and the impact of their culture and religion in envisioning future solutions.…”
Section: Discussionsupporting
confidence: 65%
“…Improving Structural Support for Refugees: Similar to previous research that has recommended considering legal and policy changes in supporting refugees' health (e.g., (Almohamed et al, 2022;Tachtler et al, 2021)), participants identified several directions for more structural changes to support refugees with disabilities and health concerns and their families. For example, P1, P2, and P4 emphasized the need for more comprehensive insurance especially for mental health support and dental care.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…HCI/CSCW studies involving the challenges of resettled refugee integration into the receiving community have been mostly conducted in the EU, reflecting the 2015 arrival of over 1 million refugees along with German Chancellor Angela Merkel's suspension of the Dublin Agreement that refugees had to seek asylum in their first country of arrival, and the denial of asylum entry to the U.S., per the Trump Administration's 2017 Muslim Ban (Executive Order 13,769 Protecting the Nation from Foreign Terrorist Entry into the United States, replaced by Order 13,070). HCI/CSCW research includes Almohamed et al (2021) comprehensive conceptual model for understanding the challenges of the refugee re-settlement experience based on an extensive literature review for informing the design of systems and services. Neuenhaus and Aly (2017), who designed EmpUP, a geolocation-based mobile game that enables Syrian refugees in Germany to connect with locals and builds empathy.…”
Section: State Of the Art: War And Human Computer Interactionmentioning
confidence: 99%